A serological method for distinguishing coagulase-negative staphylococci from micrococci - Nakhla, L. S. (1973)
Absorbed antisera prepared against heat-killed suspensions of a coagulase-negative staphylococcus and of a micrococcus were used in a slide-agglutination test. A collection of 176 coagulase-negative aerobic cocci, from which Staphylococcus aureus had been excluded, was classified into staphylococci and micrococci by means of the test for anaerobic utilization of glucose. Of 113 staphylococci, 99 reacted with the anti-staphylococcus serum, seven with the micrococcus serum, and seven with neither; of 63 micrococci, 55 reacted with the micrococcus serum and eight were untypable. Thus 161 of 176 strains (91%) were classifiable serologically, and in 154 of 161 instances (95%) the results of the serological and biochemical classification were in agreement.